Electronic Cigarettes and Cardiovascular Risk: Caution Waiting for Evidence - Domenico D’Amario; Stefano Migliaro; Josip Andjelo Borovac; Rocco Vergallo; Mattia Galli; Attilio Restivo; Matteo Bonini; Enrico Romagnoli; Antonio Maria Leone; Filippo Crea (European Cardiology Review, 2019)
Electronic cigarettes use is a growing trend in contemporary societies, with the propensity to compete with traditional tobacco smoking. Some preclinical studies demonstrated the toxic and detrimental effects of electronic cigarettes liquid components. Its impact on human health remains unknown and insufficiently studied. While some studies suggest that electronic cigarettes use might be associated with endothelial dysfunction, impaired platelet function and increased risk of adverse clinical events, other studies did not confirm these findings and epidemiological data mostly suggest that the use of electronic cigarettes appears to be safer than that of traditional tobacco cigarettes. This article provides an up-to-date overview of the current state of knowledge regarding electronic cigarettes and their impact on human health, with special emphasis on their effect on cardiovascular diseases.